Current Research in Nuclear Reactor Technology in Brazil and Worldwide 2013
DOI: 10.5772/53340
|View full text |Cite
|
Sign up to set email alerts
|

Stability of γ-UMo Nuclear Fuel Alloys by Thermal Analysis

Abstract: The development of a nuclear fuel for research reactor applications must take into account the non-proliferation of nuclear grade materials for weapons requirements, according to the Reduced Enrichment of Research and Test Reactors RERTR program. To minimize a potential problem with the use of high enriched fuels, i.e., the production of Pu and its possible utilization in nuclear weapons, several reactors have been converted their fuels from high to low enrichment. It is now acceptable a level of less than % o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…On the basis of the classical time-temperature-transformation diagrams for the binary uranium-molybdenum system, and based on the results of stability under aluminum and oxygen [11] [22], it can be suggested that compositions near or between γ-U7.5Mo and γ-U8Mo are the most gamma stable, in terms of reactions with the aluminum matrix. Since their behaviors under irradiation, according to previous works [8]- [10] [23] are almost the same in the range of 5% to 8% Mo addition.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the classical time-temperature-transformation diagrams for the binary uranium-molybdenum system, and based on the results of stability under aluminum and oxygen [11] [22], it can be suggested that compositions near or between γ-U7.5Mo and γ-U8Mo are the most gamma stable, in terms of reactions with the aluminum matrix. Since their behaviors under irradiation, according to previous works [8]- [10] [23] are almost the same in the range of 5% to 8% Mo addition.…”
Section: Discussionmentioning
confidence: 99%